Immobilized multienzymatic systems for catalysis of cascade reactions. Issue 9 (September 2016) - Ji, Qingzhi; Wang, Bochu; Tan, Jun; Zhu, Liancai; Li, Liuying
Highlights: Immobilized multienzymatic systems represent a versatile platform for biocatalysis. Considerations for constructing immobilized multienzymatic systems are reviewed. Parameters influencing immobilized multienzymatic systems are analyzed. Abstract: Cascade reactions catalyzed by immobilized multienzymatic systems are an emerging technology, making catalytic strategies more sophisticated and effective. Thus, immobilized multienzymatic systems that exploit the chemo-, regio-, and stereoselectivity of biocatalysts have been developed. Recently, a variety of bioinspired immobilized multienzymatic systems was fabricated. In this review, immobilized multienzymatic systems were divided into three types: stepwise immobilized enzymes, mixed immobilized enzymes, or co-immobilized enzymes. General considerations such as coupling pH, coupling temperature, proportion of each enzyme, and cascade bottleneck analysis for the enzymatic cascade reaction were presented. For greater insight, we analyzed the effects of substrate channeling, mass transport limitation, synergistic mechanisms, and promotion of cofactor regeneration on immobilized multienzymatic systems. Some recent novel examples of immobilized multienzymatic systems were summarized. The aim of this review is to promote and broaden the application of immobilized multienzymatic systems in biocatalysis and other related fields.